Big data and firm-level productivity: A cross-country comparison - Raphaela Andres; Thomas Niebel; Robin Sack (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2024)
Until today, the question of how digitalisation and, in particular, individual digital technologies affect productivity is still the subject of controversial debate. Using administrative firm-level data provided by the Dutch and the German statistical offices, we investigate the economic importance of data, in particular, the effect of the application of big data analytics (BDA) on labour productivity (LP) at the firm level. We find that a simple binary measure indicating the mere usage of BDA fails to capture the effect of BDA on LP. In contrast, measures of BDA intensity clearly show a positive and statistically significant relationship between BDA and LP, even after controlling for a firm's general digitalisation level.
Keywords: L25; O14; O33; 330; big data analytics; productivity; administrative firm-level data